Local Stability Analysis of a Mathematical Model of the Interaction of Two Populations of Differential Equations (Host-Parasitoid) - Anggreini, Dewi (Biology, Medicine, & Natural Product Chemistry, 2016)
Mathematical model has many benefits in life, especially the development of science and application to other fields. The mathematical model seeks to represent real-life problems formulated mathematically to get the right solution. This research is the application of mathematical models in the field of biology that examines the interaction of the two populations that host populations and parasitoid populations. This study differs from previous studies that examine the interaction of two more species that prey and predators where predators kill prey quickly. In this study the parasitoid population slowly killing the host population by living aboard and take food from the host population it occupies. In this study of differential equations are used to construct a mathematical model was particularly focused on the stability of the local mathematical model of interaction of two differential equations that host and parasitoid populations. Stability discussed in this study are stable equilibrium points are obtained from the characteristic equation systems of differential equations host and parasitoid interactions. Type the stability of the equilibrium point is determined on the eigenvalues of the Jacobian matrix. Analysis of stability is obtained by determining the eigenvalues of the Jacobian matrix around equilibrium points. Having obtained the stable equilibrium points are then given in the form of charts and portraits simulation phase to determine the behavior of the system in the future.